A Small State seeking Hard Security: Iceland, NATO and the US Defence Agreement - Ditlevsen, Martin Søvang, 1978- (2012)
Iceland has chosen to be a nation without a standing army, but in the period from 1951 to 2006 outsourced its security needs to the US through a bilateral defence agreement in the framework of NATO cooperation. In 2006 the US withdrew its forces from Iceland but kept its commitment to the defence of Iceland. While the US forces were in place, Iceland did not have to devote many resources or much independent thinking to defence and security, but this changed dramatically with the withdrawal. After 2006 the political elite of Iceland had, for the first time, to act to ensure the defence of the nation. Emphasis was initially put on re-committing the US but when that failed, attention was turned to neighbouring NATO members and eventually NATO itself. This thesis examines Iceland’s security needs as a small state without armed forces, and asks how Iceland has been positioning itself with regard to “hard” security cooperation with the US and through the NATO alliance. Based on a description of past and present circumstances, the research questions to be answered are whether the current defence agreements are suitable for Iceland in the future, and how Iceland can make sure of maximizing the security benefits from its future security cooperation. The conclusion of the thesis will reveal that so far as “hard” security goes, Iceland must place its trust in the defence agreement with the US and the NATO alliance but put effort in forming a consolidated security policy. Iceland should also focus on improving its efforts within the “soft” security areas through other international institutions. Ísland hefur kosið að vera ríki án herliðs, en á árunum 1951 til 2006 nutu Íslendingar verndar bandaríska hersins gegnum tvíhliða varnarsamning í samstarfi við NATO. Árið 2006 drógu Bandaríkjamenn herlið sitt til baka en stóðu við varnarskuldbindingu sína gagnvart Íslandi. Á meðan herlið Bandaríkjanna dvaldi hér þurftu Íslendingar ekki að taka mikla afstöðu til eða eyða miklu fé til varnar- og öryggismála, en það breyttist ...